Use of an Integrated Geochemical and Ecotoxicological Approach to Evaluate Sediment Metal Contamination in Three Protected Estuarine Areas Along the Coast of Sao Paulo State, Brazil - Capparelli, M. V.; McNamara, J. C.; Araujo, G. S. [UNESP]; Cruz, A. C. F. [UNESP]; Abessa, D. M. S. [UNESP] (Springer, 2021)
We compared sediment quality in estuaries at three locations along the coast of Sao Paulo State, Brazil, using geochemical analyses and whole sediment toxicity tests, during the southern summer and winter of 2013. Each locality is afforded a distinct degree of legal protection, and exhibits a different level of metal pollution: overall, Rio Diana (RD, the most polluted, a Permanent Protection Area) > Rio Itapanhau (RI, intermediate contamination, an Environmental Protection Area) > Rio Picinguaba (RP, pristine, a State Park). Chronic sediment toxicity tests evaluated reproductive rates of the copepod Nitokra sp. RI sediments showed the highest metal concentrations and toxicity in both seasons. Metal concentrations at RD were low but toxic in summer. RP sediments were not contaminated, suggesting effective legal protection from pollution at this locality. RI and RD, although provided some legal protection, showed clear signs of environmental degradation, emphasizing the need for more effective pollution control.
Keywords: Sediment quality; Geochemical and toxicity analyses; Legally protected reserves; Differential metal contamination; Sã o Paulo state coast